2017
DOI: 10.1021/acs.jpcb.6b12667
|View full text |Cite
|
Sign up to set email alerts
|

Confining Potential as a Function of Polymer Stiffness and Concentration in Entangled Polymer Solutions

Abstract: We directly track the tubelike motion of individual fluorescently labeled polymer molecules in a concentrated solution of unlabeled polymers. We use a single molecule wide-field fluorescence microscopy technique that is able to determine characteristic properties of the polymer dynamics, such as the confining potential, the tube diameter, and the Rouse time. The use of synthetic polymers allows us to investigate the confined motion of the polymer chains not only as a function of polymer concentration (mesh siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…4c, d , white squares). Reptation motion is characterised by a confined motion of polymer chains along virtual tube, in which the tube diameter is one of the key parameters that characterises reptation motion 42 , 43 . Given the concentration of the semi-dilute solution (10 mg ml −1 ) and the scaling law of reptation model 44 , 45 , the tracer linear chain has 158 entanglements with the matrix chains, which correspond to the entanglement length and the tube diameter of approximately 51–95 nm (see Methods for detailed calculation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4c, d , white squares). Reptation motion is characterised by a confined motion of polymer chains along virtual tube, in which the tube diameter is one of the key parameters that characterises reptation motion 42 , 43 . Given the concentration of the semi-dilute solution (10 mg ml −1 ) and the scaling law of reptation model 44 , 45 , the tracer linear chain has 158 entanglements with the matrix chains, which correspond to the entanglement length and the tube diameter of approximately 51–95 nm (see Methods for detailed calculation).…”
Section: Resultsmentioning
confidence: 99%
“…5b , see Methods for details of the analysis), further supporting the validity of the observation. A large motional freedom at the chain ends has been captured directly in previous studies using synthetic polymers 28 , 42 . In these studies, the large motional freedom at the chain ends was observed in the time scale of reptation motion (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This was calculated from the probability distribution of the transverse displacement, P ( r ), using the following equation for the confining potential in terms of the thermal energy, k B T which is based on Boltzmann statistics. 41 The confining potentials around representative filaments from four samples with different pNIPAM concentrations and temperatures are shown in Figure 3, and further similar images are shown in the Section 2 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 66%
“…Repeating this analysis lead to the same conclusion for all other sets of tube width data from nHT tracers embedded in three different background networks [22]. Although we expected to see a difference between the tube widths of entangled and crosslinked F-actin networks at the same concentration due to the suppression of fluctuation modes of crosslinked background filaments, the average values were comparable within the error bars, indicating that the fluctuations of background filaments do not have a high impact on the constraining potential exerted on the tracer filament [3,28]. By varying the persistence length l p of the tracers, we found that the expected scaling relation a ∝ l −0.2 p is not valid for all of the three examined background networks.…”
mentioning
confidence: 70%
“…Both experimental and theoretical polymer physics study how features of the constituting elements determine the properties of whole polymer networks. Previous studies have examined the interaction of semiflexible filaments [1] or investigated how geometrical parameters [2,3] and bulk mechanical properties [4] can be deduced from tracking single filaments embedded in an entangled network. However, complex semiflexible polymer networks such as the cellular cytoskeleton contain multiple types of filaments with varied mechanical properties as well as crosslinkers which create physical connections between filaments [5].…”
mentioning
confidence: 99%